2012
DOI: 10.1074/jbc.m111.332791
|View full text |Cite
|
Sign up to set email alerts
|

The Small Hydrophobic Protein of the Human Respiratory Syncytial Virus Forms Pentameric Ion Channels

Abstract: Background: Few effective treatments exist for human respiratory syncytial virus infection. The absence of small hydrophobic (SH) protein in RSV leads to viral attenuation. Results: SH protein forms pentamers and shows pH-dependent ion channel activity. Conclusion: SH protein forms pentameric ion channels. Significance: The SH protein and its channel activity constitute a potential drug target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
140
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(149 citation statements)
references
References 71 publications
(101 reference statements)
3
140
1
5
Order By: Relevance
“…SH is commonly thought to form pentameric oligomers (Collins & Mottet, 1993;Gan et al, 2008Gan et al, , 2012, although hexamers have also been reported (Carter et al, 2010). Solution NMR structures have been reported for the pentameric bundles, yet have not been added to the PDB (Gan et al, 2008(Gan et al, , 2012.…”
Section: Other Rna Virus Viroporinsmentioning
confidence: 99%
See 2 more Smart Citations
“…SH is commonly thought to form pentameric oligomers (Collins & Mottet, 1993;Gan et al, 2008Gan et al, , 2012, although hexamers have also been reported (Carter et al, 2010). Solution NMR structures have been reported for the pentameric bundles, yet have not been added to the PDB (Gan et al, 2008(Gan et al, , 2012.…”
Section: Other Rna Virus Viroporinsmentioning
confidence: 99%
“…SH is commonly thought to form pentameric oligomers (Collins & Mottet, 1993;Gan et al, 2008Gan et al, , 2012, although hexamers have also been reported (Carter et al, 2010). Solution NMR structures have been reported for the pentameric bundles, yet have not been added to the PDB (Gan et al, 2008(Gan et al, , 2012. Both SH TMD peptides and full-length protein form cation-selective channels in vitro (Gan et al, 2008), as well as promoting bacterial membrane permeability (Perez et al, 1997) and mediating dye release from liposomes (Carter et al, 2010).…”
Section: Other Rna Virus Viroporinsmentioning
confidence: 99%
See 1 more Smart Citation
“…117 HRSV small hydrophobic (SH) protein: it is thought that this protein works as an important viroporin during hRSV pathogenesis. 118 This protein also inhibits apoptosis in order to promote viral replication, as recombinant hRSV lacking the SH protein induced a significant cytopathic effect in different cell lines, compare with WT hRSV. 119 In addition, the hRSV SH has been shown to inhibit the NF-kb pathway through a decrease in the TNF-a production in mouse fibroblastic cells.…”
Section: Role Of Hrsv Proteins In Immunomodulationmentioning
confidence: 99%
“…SH is a small hydrophobic protein whose function is still unclear and is incorporated in low amounts into the virus particle (Bao et al , 2008; Gan et al , 2012). G is a heavily glycosylated and highly variable type II glycoprotein that resembles mucins and serves as the viral attachment protein (Levine et al , 1987; Thammawat et al , 2008).…”
Section: Introductionmentioning
confidence: 99%